Model Penguatan Cabang dan Ranting Muhammadiyah Berbasis Analisis Spasial dan Pendekatan Multidoor di Kabupaten Sukabumi - Prahasti Suyaman; Leonita Siwiyanti; Iqbal Noor; Winda Apriandari; Roni Renaldi Pramudita; Abdul Bari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the development patterns, implementation strategies, as well as structural and cultural challenges faced by Muhammadiyah Branch and Branch Leaders in Sukabumi Regency after the 48th Congress. As one of the largest districts in West Java, Sukabumi Regency presents complex geographical challenges for organizational consolidation. This study uses a mixed methods approach with an explanatory sequential model. Qualitative data was collected through in-depth interviews with leaders in 20 Muhammadiyah Branch Executives (PCM), while spatial analysis was used to map the organization's distribution to regional accessibility. The results of the study show that the pattern of organizational development is deterministic to the geographical location and proximity to Amal Usaha Muhammadiyah (AUM). Areas with established AUM show organic-progressive growth, while isolated areas rely on a defensive-relational model through a sono outreach strategy. Although the da'wah strategy has transformed towards philanthropy and academic collaboration, its effectiveness is still hampered by the crisis of ulama cadres, figure-centric management, and low digital literacy of senior management. This study concludes that strengthening the grassroots base requires a multidoor approach that integrates digital spatial mapping with locality-specific local economic empowerment. These findings contribute to a heterogeneous model of the development of religious organizations in rural areas to ensure the sustainability of an inclusive and enlightening tajdid movement.